Building Arrays with the Unidirectional-Radiating Complementary Strip-Slot - Hernández Escobar, Alberto; Abdo-Sánchez, María Elena; Camacho-Peñalosa, Carlos (Iñigo Cuíñas Gómez, 2021)
An upgraded version of the complementary stripslot radiating element is reviewed. The original radiating element consists in a microstrip-fed slot in transmission configuration. In the proposed modification, the slot is backed by a cavity in order to obtain unidirectional radiation. The presence of this cavity changes the behavior of the slot. A new equivalent circuit is used to propose a design methodology for broadband operation. Two array designs are simulated and implemented: a phased array and a log-periodic array. Promising experimental results verify the unidirectional radiation and the wide bandwidth of these antennas.
This work was supported by the Spanish Ministerio de Educación, Cultura y Deporte (Programa para la Formación del Profesorado Universitario) under grant FPU15/06457, by the Spanish Ministerio de Ciencia, Innovaci´on y Universidades (MCIU) (Contrato Juan de la Cierva-Incorporaci´on) under Grant IJC2018-038440-I, and by the MCIU, AEI, and FEDER (Programa Estatal de I+D+i Orientada a los Retos de la Sociedad) under grant RTI2018-097098-J-I00.
Keywords: Antenas; Array; Antena; Strip-slot complementario